PENENTUAN LABA PADA TRANSAKSI BISNIS BERBASIS BUDAYA MAROSOK - Pebrian, Rinto; Wifarsyah, Rindo; Firdaus, Kurnia (Prosiding Seminar Nasional: Manajemen, Akuntansi, dan Perbankan; Vol 1 No 1 (2018): Prosiding Seminar Nasional dan Call for Papers Manajemen, Akuntansi, dan Perbankan 2018, 2018)
This study aims to determine the determination of profit on Marosok Culture based-business transactions in Livestock Market Manggis, Lubuk Basung, Kab. Agam by using descriptive qualitative method. The informants were selected using judgmental sampling and snowball sampling techniques. Data was obtained through in-depth interview, observation, documentation and literature study. The technical data analysis by collecting data, describe, analyze, and do interpretation. The result showed that the determination of profit in marosok culture based business transaction as follows: (1) Seller from the side of toke livestock or businessman, profit is determined from the difference of selling price of livestock with total cost they spend, whereas seller from breeder side usually not too count on profit in transactions marosok. (2) Buyers from the side of butcher, profit is determined based on the accuracy of patuik dagiang they do, whereas buyer from breeder side, profit is determined based on accuracy patuik dipataranakan done in transactions marosok.